KARAKTERISTIK INDUSTRI KECIL MANUFAKTUR DAN DAMPAKNYA TERHADAP NILAI PRODUKSI DI PROVINSI KALIMANTAN TIMUR - Roy, Juliansyah (FORUM EKONOMI, 2016)
This research aims to: 1) identifies the characteristics of manufacturing industries of their working capital, compensation, and type of business; 2) analyzes the impact of manufacturing industries towards production values in East Kalimantan. The analysis method used is linier regression with cross section data in the east Kalimantan province. The study shows that: 1) working capital has significant positive effect towards the production value of small manufacturing industries in the east Kalimantan province. 2) Compensation does not affect the production value of small manufacturing industries in the east Kalimantan province; 3) types of business does not affecting the production value of small manufacturing industries in the east Kalimantan province.Keyword: Working Capital; Compensation; Type of Business, and Productions